Central American School Athletes: Identification and Detection Process Talent Atletas Escolais Central Americanos: Processo de Identificação e Detecção de Talentos (Impetus, 2021)
The previous measurement of characteristics associated with athletic performance is necessary to ensure that those who start the preparation process have the necessary postulates for success. Objective: To establish whether the participants in the IV Central American and Caribbean School Games done in Armenia, Colombia, in 2013 were selected from objective tests to determine the level of sporting talent. Method: Quantitative study with cross-sectional and descriptive scope. Population and sample: On behalf of 683 participants were surveyed an intentional sample of 233 athletes from nine countries, mean age 16.9 ± 0.76 years, 7.26 ± 3.27 sport years old. The survey was developed by the research group and subjected to expert judgment. Participation was voluntary. The information was processed with SPSS v.17 program. Results: 2 out of 3 participants answered a skills assessment procedure; the most used measures were anthropometric followed by fitness tests and technical skills. Only to 1 in 6 were applied tests to all critical factors in athletic performance. As a trend, the top-ranked countries by gold medals showed greater use of tests for the identification of sports skills.